Busting the Myth that Pilots Never Scale - Prager, Steven D (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Busting the Myth that Pilots Never Scale: Unpacking the USAID Climate Services for Resilient Development Strategy in LAC. Presented at the International Conference on Climate Services version 6 (ICCS6).